Confocal micro-PIV measurements of blood flow in microchannels - Lima, R. (2010)
The detail measurements of velocity profiles of blood flow in microchannels are fundamental for a better understanding on the biomechanics of the microcirculation. It is therefore very important to obtain measurements with high accuracy and spatial resolution of the influence of the blood cells on the plasma flow behaviour. This paper presents and compares measurements of in vitro blood with different hematocrits within a square microchannel obtained by a confocal particle image velocimetry (PIV) system. This emerging technology by combining the conventional PIV system with a spinning confocal microscope has the ability to obtain not only high spatial resolution images but also three-dimensional (3D) optical sectioning velocity measurements. Velocity measurements of plasma seeded with 1 ~tm diameter fluorescent particles were performed at different locations along the depth of 100 ~tm square microchannel at a constant flow rate (0.15~tl/min) and Reynolds number (Re) of 0.025. By using our confocal micro-PIV system, it was possible to obtain time-series of instantaneous velocity profiles with high spatial resolution of 28.24 18.83 ~tm at time intervals of 5 ms between two images. The ensemble-averaged velocity results of blood flow with different hematocrits (up to 25%) have shown velocity profiles very close to a parabolic shape. However, by analysing the temporal variance of the instantaneous velocity profiles of different hematocrits, we have observed a substantial increase of the instantaneous velocity fluctuations by increasing the hematocrit within the plasma flow. Besides, some possible effects from the measurements accuracy and flow rate instabilities from the syringe pump, this observation also suggests that there is a direct correlation between the level of hematocrit and the temporal instantaneous velocity fluctuations.